2020
DOI: 10.3390/app10186425
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-Based Prediction of Overall Survival in Lung Cancer Using Different Volumes-Of-Interest

Abstract: Lung cancer accounts for the largest amount of deaths worldwide with respect to the other oncological pathologies. To guarantee the most effective cure to patients for such aggressive tumours, radiomics is increasing as a novel and promising research field that aims at extracting knowledge from data in terms of quantitative measures that are computed from diagnostic images, with prognostic and predictive ends. This knowledge could be used to optimize current treatments and to maximize their efficacy. To this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Different ensemble ML using CT radiomics features were investigated for prediction of overall survival in patients with Non-Small Cell Lung Cancer [11]. Interestingly, the accuracy improved when using the clinical target volume, confirming the hypothesis that, in the surroundings of the visible tumor, there is useful information to predict patients' outcome [6]. A retrospective study recently started in the framework of Artificial Intelligence in Medicine (AIM), a project founded by INFN, aims to investigate imaging and dose biomarkers for clinical outcome of pediatric patients affected by medulloblastoma who underwent Cranio-Spinal Irradiation (CSI) using Helical Tomotherapy [163].…”
Section: Cancer Prognosis and Therapy Outcome Predictionmentioning
confidence: 66%
See 1 more Smart Citation
“…Different ensemble ML using CT radiomics features were investigated for prediction of overall survival in patients with Non-Small Cell Lung Cancer [11]. Interestingly, the accuracy improved when using the clinical target volume, confirming the hypothesis that, in the surroundings of the visible tumor, there is useful information to predict patients' outcome [6]. A retrospective study recently started in the framework of Artificial Intelligence in Medicine (AIM), a project founded by INFN, aims to investigate imaging and dose biomarkers for clinical outcome of pediatric patients affected by medulloblastoma who underwent Cranio-Spinal Irradiation (CSI) using Helical Tomotherapy [163].…”
Section: Cancer Prognosis and Therapy Outcome Predictionmentioning
confidence: 66%
“…Machine learning (ML) is a field of AI algorithms (Fig. 1) which can recognize patterns in medical images by analyzing voxel intensity values or quantitative imaging features, called also "radiomic features", by identifying their best combination and building a model for classification or regression [3][4][5][6]. By ML, image features can also be combined with variables from other sources, such as dose distribution from the radiotherapy treatment [7]) or clinical variables [8] to improve accuracy of classification.…”
Section: Machine Learning and Deep Learning In Imagingmentioning
confidence: 99%
“…A total of 433 studies were identified, in which 432 studies were identified by the comprehensive literature search and one study was identified by a hand search of the relevant literature. After screening and evaluating, 13 studies with 2942 patients meeting the criteria were included in this systematic review [22,23,[27][28][29][30][31][32][33][34][35][36][37].…”
Section: Literature Search and Data Extractionmentioning
confidence: 99%
“…The included studies were published from 2017 to 2022. Almost all the studies (12/13, 92%) were retrospectively designed [22,23,[27][28][29][30][31][32][33][34][35][36], except one of the studies, which was prospective [37]. Patients from seven studies (7/13, 54%) were from one center [22, 28-30, 34, 36, 37], and the others (6/13, 46%) were from multiple center [23,27,[31][32][33]35].…”
Section: Patient and Study Characteristicsmentioning
confidence: 99%
“…Radiomics leverages on artificial intelligence techniques and the increasing availability of large, open-access and multicentric datasets of pre-classified cases to infer clinical information about unknown ones (‘population imaging’ approach [ 13 ]). Several studies have underlined the potential benefit of radiomics for clinical problem-solving in lung cancer, such as prediction of malignancy [ 14 , 15 , 16 ], histological subtype [ 17 , 18 , 19 ], prognosis [ 20 , 21 , 22 ] and response to treatment [ 23 , 24 , 25 ] (see also Figure 1 for an overview of potential applications).…”
Section: Introductionmentioning
confidence: 99%